A case of Russell body gastritis with multifocal lesions - Umakoshi, Michinobu (SAGE Open Med Case Rep, 2020)
Russell body gastritis is an extremely rare gastritis characterized by abundant infiltration of plasma cells with Russell body and eccentric nuclei, known as Mott cells. An 81-year-old Japanese woman with Helicobacter pylori and hepatitis C virus infection complaining of abdominal discomfort underwent upper gastrointestinal endoscopy, which detected an elevated lesion 2 cm in diameter at the anterior wall of the gastric body. A histological examination of the lesion revealed the infiltration of numerous Mott cells with an abundant eosinophilic crystal structure and eccentric nuclei in the lamina propria, resulting in a pathological diagnosis of Russell body gastritis. Endoscopic submucosal dissection (ESD) was performed subsequently. The histological findings of the resected specimen were compatible with those of Russell body gastritis. Upper gastrointestinal endoscopy performed 2 months after endoscopic submucosal dissection revealed the presence of new multiple flat elevated lesions in the antrum up to 1 cm in diameter, distant from the site of endoscopic submucosal dissection. A histological examination revealed a few Mott cells in the biopsy specimens taken from the new lesions. In turn, H. pylori eradication therapy was performed 1 month after the detection of the new lesions. One year after the eradication therapy, follow-up upper gastrointestinal endoscopy revealed that multiple lesions had almost disappeared, and the histological examination of the gastric biopsy specimens confirmed the disappearance of Mott cells. We herein report a case of Russell body gastritis in which multifocal lesions were observed after endoscopic submucosal dissection, and which was subsequently treated by H. pylori eradication therapy.